Sex-Dependence in the Effect of Pharmaceutical Excipients: Polyoxyethylated Solubilising Excipients Increase Oral Drug Bioavailability in Male but not Female Rats - Yang Mai; Liu Dou; Christine M. Madla; Sudaxshina Murdan; Abdul W. Basit (MDPI AG, 2019)
It is known that males and females respond differently to medicines and that differences in drug behaviour are due to inter-individual variability and sex specificity. In this work, we have examined the influence of pharmaceutical excipients on drug bioavailability in males and females. Using a rat model, we report that a portfolio of polyoxyethylated solubilising excipients (polyethylene glycol 2000, Cremophor RH 40, Poloxamer 188 and Tween 80) increase ranitidine bioavailability in males but not in females. The in vivo sex and excipient effects were reflected in vitro in intestinal permeability experiments using an Ussing chamber system. The mechanism of such an effect on drug bioavailability is suggested to be due to the interaction between the excipients and the efflux membrane transporter P-glycoprotein (P-gp), whose expression in terms of gene and protein levels were inhibited by the solubilising agents in male but not in female rats. In contrast, the non-polyoxyethylated excipient, Span 20, significantly increased ranitidine bioavailability in both males and females in a non-sex-dependent manner. These findings have significant implications for the use of polyoxyethylated solubilising excipients in drug formulation in light of their sex-specific modulation on the bioavailability of drugs that are P-gp substrates. As such, pharmaceutical research is required to retract from a ‘one size fits all’ approach and to, instead, evaluate the potential impact of the interplay between excipients and sex on drug effect to ensure effective pharmacotherapy.